Obesity and Disease Severity among COVID 19 Cases: A Hospital Based Study - Dahal, Aashma; Karki, Nabina (Nepal Journal of Health Sciences, 2022)
Introduction: According to World Health Organization report obesity has tripled between 1975 and 2016. The COVID-19 pandemic has occurred at a time when the prevalence of individuals with overweight/obesity is increasing at an unprecedented rate throughout all the continents.Objectives: This research aims to explore increased BMI (obesity) as a potential cause for COVID-19 disease severity in hospitalized patients by looking at the association between these two variables.Methods: It is a cross sectional analytical study which aims to assess the association between obesity and COVID-19 case severity in hospitalized patients of Hetauda Hospital.Results: 30.4 percent of the COVID-19 hospitalized cases had normal weight, 44.6 percent of them were obese, 17.4 percent were overweight whereas 7.6 percent of the admitted patients were underweight. Only 1 was mild case (1.1%), 52 participants (56.52%) were moderately severe cases and 39 (42.39%) cases of the 92 research participants were critically severe. Fisher Exact tests were performed to find the association between BMI and disease severity as categorical variables which showed that there was no significant association between the two variables (Fisher exact value=0.665).Conclusions: This study concludes that there is no association in between obesity and COVID-19 disease severity. However, this relationship should be further explored by research studies with more sample size.